IN VITRO SCREENING OF ANTI-CANDIDA ACTIVITY OF SAPONINS EXTRACTED FROM GLYCYRRHIZA GLABRA AND QUILLAJA SAPONARIA - Moghimipour, Eskandar; Sadaghi-Nejad, Batool; Handali, Somayeh; Ameri, Abdulghani; Ramezani, Zahra; Ebrahim Azemi, Mohammad (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: In recent years, the incidences of opportunistic fungal pathogens have increased and development of fungal resistance to antifungal drugs is a global concern. Therefore, it is important to identify new antifungal agents. Saponins are secondary metabolites that are found in various plant species and show antifungal activity. The aim of the study was to evaluate antifungal activity of saponin extracted from the Glycyrrhiza glabra against Candida species (Candida albicans, Candida tropicalic and Candida glabrata). Antifungal activity Quillaja saponaria total saponin (QST) was also evaluated. Methods: The roots of the plant were dried, powdered and def-fatted with petroleum ether in a soxhlet apparatus. The air dried powder was successively extracted with methanol, n-butanol and diethyl ether. The antifungal activity of the saponins was carried out using well diffusion method and also the value of minimum inhibitory concentrations (MIC) was calculated. Clotrimazole was used as positive controls to determine the sensitivity of the species. Results: According to the results, C. albicans, and C. tropicalic were sensitive to the saponins of G. glabra, and Q. saponaria, while saponin isolated from G. glabra just could inhibited the growth of C. glabrata. Conclusion: In vitro studies have demonstrated that saponins extracted from G. glabra, and Q. saponaria can serve as potential candidates for the development of new antifungal agents. Â  Â  Key words: Saponin, Glycyrrhiza glabra, Quillaja saponaria, Anti-Candida activity